2014
DOI: 10.1128/cvi.00501-14
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Human Immunodeficiency Virus Infection on Plasma Bactericidal Activity against Salmonella enterica Serovar Typhimurium

Abstract: b Individuals with human immunodeficiency virus (HIV) infection have increased susceptibility to invasive disease caused by Salmonella enterica serovar Typhimurium. Studies from Africa have suggested that this susceptibility is related in part to the development of a high level of lipopolysaccharide (LPS)-specific IgG that is able to inhibit the killing of S. Typhimurium by bactericidal antibodies in healthy individuals. To explore this issue further, we examined the bactericidal activity against S. Typhimuriu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Trebicka et al have recently described the absence of killing of S . Typhimurium by sera from HIV-infected Americans associated with a lack of IgG antibodies to LPS [ 33 ], rather than the high levels of these antibodies that we have found in HIV-infected Africans. This is consistent with the concept that some, but not excessive, antibodies to LPS are required to kill Salmonella .…”
Section: Discussionmentioning
confidence: 79%
“…Trebicka et al have recently described the absence of killing of S . Typhimurium by sera from HIV-infected Americans associated with a lack of IgG antibodies to LPS [ 33 ], rather than the high levels of these antibodies that we have found in HIV-infected Africans. This is consistent with the concept that some, but not excessive, antibodies to LPS are required to kill Salmonella .…”
Section: Discussionmentioning
confidence: 79%
“…Several immune defects have been contributed to the susceptibility of HIV-infected individuals to NTS bacteremia. These include the depletion of CD4 + , loss of IL-17-producing CD4 + T cells in the gut mucosa,7 and dysregulated excess production of anti-lipopolysaccharide immunoglobulin G that inhibits serum killing of extracellular Salmonella in a concentration-dependent fashion 23,31. In the present study, HIV-infected individuals who had a CD4 + count <200 cells/µL was 3.6 times more likely found to be infected with NTS bacteria (AOR: 3.61, 95% CI: 1.74–5.25).…”
Section: Discussionmentioning
confidence: 99%
“…Typhimurium as the antigenic target of the bactericidal antibodies, and showed that both serum bactericidal activity and the levels of anti- S . Typhimurium LPS antibodies were significantly reduced in young children and in subsets of HIV-infected adults (10,11). The near-universal presence of antibodies against S .…”
Section: Introductionmentioning
confidence: 99%